Microtubule associated protein 4 phosphorylation leads to pathological cardiac remodeling in miceResearch in context - Lingfei Li (EBioMedicine, 2018)
Background: Cardiac remodeling is a pathophysiological process that involves various changes in heart, including cardiac hypertrophy and fibrosis. Cardiac remodeling following pathological stimuli is common trigger leading to cardiac maladaptation and onset of heart failure, and their pathogenesis remains unclear. Methods: Heart specimens of tetralogy of Fallot (TOF) patients, myocardial infarction (MI) and transverse aortic constriction (TAC) mouse models were collected to determine changes of microtubule associated protein 4 (MAP4) phosphorylation. MAP4 (S667A, S737E and S760E) knock in (MAP4 KI) mouse and cultured neonatal mouse cardiomyocytes or fibroblasts were used to investigate changes of cardiac phenotypes and possible mechanisms with a variety of approaches, including functional, histocytological and pathological observations. Findings: Elevated cardiac phosphorylation of MAP4 (S737 and S760) was observed in TOF patients, MI and TAC mouse models. In MAP4 KI mice, age-dependent cardiac phenotypes, including cardiac hypertrophy, fibrosis, diastolic and systolic dysfunction were observed. In addition, increased cardiomyocyte apoptosis together with microtubule disassembly and mitochondrial translocation of phosphorylated MAP4 was detected prior to the onset of cardiac remodeling, and p38/MAPK was demonstrated to be the possible signaling pathway that mediated MAP4 (S737 and S760) phosphorylation. Interpretation: Our data reveal for the first time that MAP4 drives pathological cardiac remodeling through its phosphorylation. These findings bear the therapeutic potential to ameliorate pathological cardiac remodeling by attenuating MAP4 phosphorylation. Fund: This work was supported by the Key Program of National Natural Science Foundation of China (No.81430042) and National Natural Science Foundation of China (No.81671913). Keywords: MAP4, Cardiac remodeling, Apoptosis, Mitochondria, Microtubule